2010
DOI: 10.2535/ofaj.87.33
|View full text |Cite
|
Sign up to set email alerts
|

False positive reactivity of a substance P-antibody in the ectodermal/epithelial plug of the nose, ear, eye and perineum of the human and mouse fetuses

Abstract: Summary:The main aim of this review is (1) to introduce the two previous studies we published human lower limb anatomy based on the conventional macroscopic anatomical criteria with hazardous recognition of this description, (2) to activate the discussion whether the limb homology exists, and (3) to contribute to future study filling the gap between the gross anatomy and embryology.One of the topic we discussed was the human persistent sciatic artery. To date, numerous human cases of persistent sciatic artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…No macrophages in the keratinocyte plug at the external ear and nose was one of the striking features. Because of no reaction of the keratinocyte plug found using deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end-labeling method, Masumoto et al [ 12 ] hypothesized a substance-P mediated cell death, but they themselves found that non-specific immunoreactivity was likely to bring their result. Cornification is a highly specific type of programmed cell death [ 1 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No macrophages in the keratinocyte plug at the external ear and nose was one of the striking features. Because of no reaction of the keratinocyte plug found using deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end-labeling method, Masumoto et al [ 12 ] hypothesized a substance-P mediated cell death, but they themselves found that non-specific immunoreactivity was likely to bring their result. Cornification is a highly specific type of programmed cell death [ 1 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the thickness of keratinocyte layer is much thicker than the usual skin. Second, according to Masumoto et al [ 12 ], most or all of the keratinocytes most likely to carry cell nucleus in the plugs, in contrast to lost nuclei in the usual cornified layer of skin.…”
Section: Introductionmentioning
confidence: 99%
“…Although periprostatic nerve fibers negative for both nNOS and TH have been described as “somatic nerve fibers” (Costello et al, ), a better term may be “sensory nerves”. To our regret, we could not immunohistochemically assess the expression of sensory nerve markers, such as substance P and CGRP, in our donated cadaver specimens (partly published in Masumoto et al, ). We observed mixed nerves, containing both sympathetic and parasympathetic elements, not only in the intermuscular space of the rectum but also in the intersphincteric space below the epithelial junction.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the embryonic nasal plug is a common transient embryonic feature of amniotes. It has been found in snakes [66,69,72], lizards [18,73], turtle [69], Sphenodon [74], birds [71,72] and mammals [72,75] including human [76,77]. The nature of the nasal plug is poorly understood.…”
Section: Initial Fusion and Formation Of The Vestibulummentioning
confidence: 99%
“…The nature of the nasal plug is poorly understood. It is described as mass of epithelial cells [75], mass of isodiametric cells [21], peridermal plug [72,78], or structure formed by keratinocytes [77]. It has been proposed that it forms between the nasal prominences from the epithelial seam, which does not undergo disintegration [71,72], or as a proliferation of the "invaginated" oral epithelium [78], which in fact may be considered as walls of the presumptive vestibulum.…”
Section: Initial Fusion and Formation Of The Vestibulummentioning
confidence: 99%